Spontaneous Resolution of Massive Spontaneous Tubercular Pneumothorax - Surya Kant; S. Saheer; G. Hassan; Jabeed Parengal (Case Reports in Pulmonology)
A 29-year-old female presented with complaints of fever and productive cough of three weeks duration. Pulmonary tuberculosis was diagnosed bacteriologically and she was prescribed antituberculosis drugs. During follow-up she developed massive pneumothorax, for which patient refused surgical management and was managed conservatively. After six months there was complete spontaneous resolution of pneumothorax. The unusual presentation and unexpected outcome prompted us to report this case.